2004
DOI: 10.1111/j.1349-7006.2004.tb03245.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro conversion of irinotecan to SN‐38 in human plasma

Abstract: Irinotecan is an active cytotoxic agent for various cancers, and is converted to SN-38, its most active metabolite, by carboxylesterase converting enzyme (CCE) in vivo. Although the primary metabolic site is in the liver, ex vivo studies have proven that irinotecan is also converted to SN-38 in intestines, plasma and tumor tissues. The present study attempted to elucidate the in vitro conversion efficiency in human plasma, and to examine possible inter-individual variability and its clinical significance. Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…The actual levels of DNA damage produced both in cancer and non‐target cells in human evidently are much higher due to the presence of SN‐38, a metabolite with an augmented potency and cytotoxicity [26]. While the present study was performed in vitro , and the blood cells were exposed to irinotecan in a serum‐free medium, there was no possibility for extensive conversion of the parent drug to SN‐38, although some studies indicate that human plasma esterases, especially butyrylcholinesterase, present in serum also possess irinotecan‐activating activity [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…The actual levels of DNA damage produced both in cancer and non‐target cells in human evidently are much higher due to the presence of SN‐38, a metabolite with an augmented potency and cytotoxicity [26]. While the present study was performed in vitro , and the blood cells were exposed to irinotecan in a serum‐free medium, there was no possibility for extensive conversion of the parent drug to SN‐38, although some studies indicate that human plasma esterases, especially butyrylcholinesterase, present in serum also possess irinotecan‐activating activity [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Conversion of irinotecan to SN-38 can be mediated by several esterases (32), which are usually synthesized in the liver, but some also in the small intestine and kidney (29,33). Therefore, we tested expression levels by real time PCR of all obvious candidate carboxylesterase, paraoxonase, and butyrylcholinesterase genes (34) in the liver, small intestine, and kidney of wild-type and Oatp1a/1b knockout, but also of liver-specific humanized OATP1B1 and OATP1B3 transgenic mice (Fig.…”
Section: H)mentioning
confidence: 99%
“…Guemei et al (15) highlighted an association between the specific plasma esterase activity and SN38 AUC. Conversely, Shingoji et al (26) reported no association between the activity of CPT11 hydrolase in plasma (mediated by CES) and the AUC of SN38 in cancer patients.…”
Section: Discussionmentioning
confidence: 99%